Physiological basis in the assessment of myocardial mechanics using speckle-tracking echocardiography 2D. Part II - Wojciech Mądry; Maciej Aleksander Karolczak (Journal of Ultrasonography, 2016)
In this paper, the authors attempt to concisely present the anatomical and pathophysiological bases as well as the principles for echocardiographic evaluation of mechanical aspects of cardiac function based on speckle tracking method. This technique uses a phenomenon involving the formation of characteristic image units, referred to as speckles or acoustic markers, which are stable during cardiac cycle, on a two-dimensional echocardiographic picture. Changes in the position of these speckles throughout the cardiac cycle, which are monitored and analyzed semi-automatically by a computer system, reflect deformation of both, cardiac ventricle as a whole as well as its individual anatomical segments. The values of strain and the strain rate, as well as the range and velocity of the movement of these markers, which are in close relationship with multiple hemodynamic parameters, can be visualized as various types of charts – linear, two- and three-dimensional – as well as numerical values, enabling deeper insight into the mechanical and hemodynamic aspects of cardiac function in health and disease. The use of information obtained based on speckle tracking echocardiography allows to understand previously unclear mechanisms of physiological and pathophysiological processes. The first part of the study discusses the formation of a two-dimensional ultrasound image and the speckles, as well as the technical aspects of tracking their movement. The second part presents in more detail the methodology of speckle-tracking echocardiography, the characteristic abnormalities of cardiac mechanics presenting in different clinical entities, and the limitations related to given clinical and technical issues.